2022
DOI: 10.54371/jiip.v5i1.396
|View full text |Cite
|
Sign up to set email alerts
|

Tinjauan Kritis terhadap Ontologi Ilmu (Hakikat Realitas) dalam Perspektif Sains Modern

Abstract: Penelitian ini menjelaskan tentang tinjauan kritis terhadap ontologi ilmu (hakikat realitas) dalam perspektif sains modern. Ontologi mempelajari tentang objek apa yang ditelaah ilmu, perwujudannya dan hubungannya dengan daya tangkap manusia, sehingga dapat menghasilkan ilmu pengetahuan. Metode yang digunakan dalam kajian ini menggunakan metode atau pendekatan kepustakaan (library research), bahwa studi pustaka atau kepustakaan dapat diartikan sebagai serangkaian kegiatan yang berkenaan dengan metode pengumpula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Humans are spiritual centers and are interconnected with other spiritual levels, so it can be concluded that these levels are also spiritual centers. The state of physical objects will be imperfect and will not lead to a true truth (Nurasa et al 2022).…”
Section: A Ontology Orientationmentioning
confidence: 99%
“…Humans are spiritual centers and are interconnected with other spiritual levels, so it can be concluded that these levels are also spiritual centers. The state of physical objects will be imperfect and will not lead to a true truth (Nurasa et al 2022).…”
Section: A Ontology Orientationmentioning
confidence: 99%